Model Kelayakan Investasi Sentra Umkm Mix-Used Mendukung Peningkatan Pendapatan Daerah - Joko Suyono; Suhermin Suhermin; Agus Sukoco; M. Ikhsan Setiawan (IAI Darussalam, 2017)
City and District governments in Indonesia would take the initiative in order to increase local revenue, in addition, to improve the performance of SMEs, but also to cooperate with the investors to take advantage of regional assets into Sentra SMEs. This research aims to develop SMEs Sentra Investment Feasibility Model Mix-Used in areas with Fuzzy Logic as a strategy to increase the prosperity of the region under the ASEAN Economic Community. The study was conducted in two (three) years, the first year is to conduct a feasibility analysis of investment Sentra Mix-Used, in order to support increased local revenues in East Java and Indonesia's research results published in the Seminar / Proceedings International, International Journal indexed by Scopus, and submitted to the Ministry law and Human Rights to obtain IPR Copyright on Investor application model Mix-used Sentra SMEs using Fuzzy Logic.